การใช้สารสกัดจากมะระขี้นก (Momordica charantia) ร่วมกับอินซูลินในการรักษาสุนัขที่ป่วยเป็นเบาหวาน : รายงานผลการวิจัย - ศิรินทร หยิบโชคอนันต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
To investigate the effect of the Momordica charantia capsule, combined with low-carbohydrate, high fiber diet and insulin on the treatment of naturally occurring diabetes mellitus in dogs. Twenty-five client-owned dogs with naturally occurring diabetes mellitus were entered into the study. Each dog was fed a commercially available low-carbohydrate, high fiber diet and received insulin subcutaneously once a day over the course of 5 month of study. The dogs were divided into two groups, one was the diabetic control (DC) group (n = 5) and the other was the Momordica charantia treated (DMC) group (n = 20). The DMC group received 2,000 mg/10 kg BW of Momordica charantia (MC) capsule orally every day with meal for two consecutive months, and then the dosage of MC capsule was increased to 4,000 mg/10 kg BW for other 2 months. The fasting glucose levels, serum fructosamine, serum chemistry profiles and complete blood count were determined and serial blood glucose curve was performed to adjust insulin dosage for individual requirement monthly for 5 months. The results showed that, after receiving the MC capsule (2,000 mg/10 kg BW) for 1 and 2 months respectively, the serum fructosamine levels were significantly lower than those in the control group and those in the month before treatment. The fasting blood glucose level was slightly decreased after receiving the MC capsule for one month, and a statistical difference compared to those in the month before treatment was observed after receiving the MC capsule for two months. In contrast, the fasting blood glucose and serum fructosamine levels after receiving 4,000 mg/10 kg BW for 2 months were increased, in which they were not significantly different compared to those in the month before treatment. The complete blood count and serum chemistry profiles were not different in comparisons between these two groups, except for alkaline phosphatase enzyme (ALP) levels. The ALP levels in the DMC group were significantly higher then those in the control group for the whole study. All dogs in the DMC group were later classified as responders (serum fructosamine level <= 450 micro mol/L and/or insulin requirement was decreased, n=12) and non-responders (serum fructosamine level > 450 micro mol/L and continue to require insulin at the same dose, n=8). Our findings suggested that the use of the MC capsule at 2,000 mg/10 kg BW combined with low-carbohydrate, high fiber diet improved glycemic control and slightly decreased exogenous insulin usage in naturally occurring diabetes mellitus dogs.